2014
DOI: 10.1074/mcp.m113.036301
|View full text |Cite
|
Sign up to set email alerts
|

The Intraviral Protein Interaction Network of Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) is a global health problem and one of the main reasons for chronic liver diseases such as cirrhosis and hepatocellular carcinoma. The HCV genome is translated into a polyprotein which is proteolytically processed into 10 viral proteins. The interactome of the HCV proteins with the host cell has been worked out; however, it remains unclear how viral proteins interact with each other. We aimed to generate the interaction network of these 10 HCV proteins using a flow-cytometrybased FRET as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 89 publications
0
35
0
1
Order By: Relevance
“…Importantly, the method allows the measurement of protein interactions in living cells, and independently and multiple times, we confirmed FRET-measured interactions by biochemical assays and in virus-infected cells, demonstrating that FACS-FRET is a robust assay to assess protein interactions (21,26,27). Briefly, 150,000 293T cells were seeded in a 12-well plate and transfected 12 h later.…”
Section: Facs-fretmentioning
confidence: 96%
“…Importantly, the method allows the measurement of protein interactions in living cells, and independently and multiple times, we confirmed FRET-measured interactions by biochemical assays and in virus-infected cells, demonstrating that FACS-FRET is a robust assay to assess protein interactions (21,26,27). Briefly, 150,000 293T cells were seeded in a 12-well plate and transfected 12 h later.…”
Section: Facs-fretmentioning
confidence: 96%
“…Recently, it has been proposed that the cellular Ewing sarcoma breakpoint region 1 (EWSR1) protein is important for regulation of the switch from translation to replication by binding to the cis-acting replication element of HCV (14). Furthermore, transport of HCV Core toward LDs by the enzyme diacylglycerol acyltransferase-1 (DGAT1) is crucial for production of newly formed virions (15, 16), and the NS2 protein, together with p7, might be a major player in coordinating assembly (11,17,18).How HCV is released from infected cells is still under debate.HCV was found to associate with constituents of very-low-density lipoproteins (VLDL), such as , and proteins of the VLDL secretory pathway, including the transcription factor hepatocyte nuclear factor 4 (HNF4) (22). Thus, it has been assumed that HCV budding, maturation, and release might intersect the VLDL secretion pathway (13), but a precise model is still lacking and a recent study suggested that HCV release is independent of the VLDL route (23).…”
mentioning
confidence: 99%
“…Recently, it has been proposed that the cellular Ewing sarcoma breakpoint region 1 (EWSR1) protein is important for regulation of the switch from translation to replication by binding to the cis-acting replication element of HCV (14). Furthermore, transport of HCV Core toward LDs by the enzyme diacylglycerol acyltransferase-1 (DGAT1) is crucial for production of newly formed virions (15, 16), and the NS2 protein, together with p7, might be a major player in coordinating assembly (11,17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While most previous studies have been conducted in the wellcharacterized HeLa cell model, providing a good rational for molecular and cell biological experiments, our goal was to clarify the roles of the different cellular proteins in cells relevant to HIV-1 infection, such as the CD4 ϩ T cell line SupT1 and primary CD4 ϩ T cells. Furthermore, we aimed to investigate binding of host cell factors with Nef by our established fluorescence-activated cell sorter (FACS)-Förster resonance energy transfer (FRET) assay, allowing detection of transient protein interactions in living cells (16,17). We utilized cyan fluorescent protein (CFP)-tagged variants of the adaptor protein subunits AP-1, AP-2, AP-2, and AP-3; the thioesterase ACOT8; ␤-COP; the ATPase V1H; and CD4 (all ligated into Clontech pECFP/EYFP vectors as described previously [16]).…”
mentioning
confidence: 99%